A rare case of femoral Richter’s hernia - Aher, Kalyani Dnyaneshwar; Gadhire, Minakshi; Yadav, Ashish Kumar Lallan Prasad; Manek, Miit Raju (International Surgery Journal, 2025)
Among all abdominal hernias, femoral hernia is a relatively rare type, occurring more commonly in elderly female. Femoral Richter’s hernia refers to a condition in which small portion of the bowel circumference becomes entrapped with in the sac of a femoral hernia. We hereby present the case of a 79 years old female with a strangulated femoral Richter’s hernia, who presented without typical symptoms of bowel obstruction and its emergency operative management.